Characteristics and Applications of Sea Water Reverse Osmosis Reject Water of PT Cirebon Electric Power as Voltaic Cell Electrolyte and Salt Raw Material - Dimas Agung Pramudikto; Satya Nugroho; Agik Dwika Putra; Ilham Satria Raditya Putra; Sigit Setyawan; Teguh Ariyanto (Eksergi, 2022)
Sea Water Reverse Osmosis (SWRO) reject water produced by PT Cirebon Electric Power has not been optimally utilized. In this research, a study of the characteristics of SWRO reject water was carried out to determine important properties such as turbidity, conductivity, pH and salinity. This characteristic is important as a basis for consideration of SWRO reject water applications. In addition, data were taken from a fairly long period of 5 years of SWRO operation (2016-2021) so that the consistency of the data can be known. The results showed that SWRO reject water had low turbidity (0.18±0.08 NTU), high conductivity of ca. 76.000 µS/cm, neutral pH and high salinity (4.6±0.3%). The study of the utilization of SWRO reject water was then carried out, namely as an electrolyte for salt water lamps and as raw material for making salt. The results showed that SWRO reject water can be used as an electrolyte for salt water lamps which produces a voltage potential up to 1.4 Volts (20% higher than seawater electrolyte). As a raw material for salt, the salt produced has excellent characteristics (eg 99% NaCl) and complies with SNI 3556:2016, except for the KIO3 content.